The Quality of the First Components [i̱], [u̱] of Acuted Diphthongs in the Lukšiai Subdialect - Bacevičiūtė, Rima (Kalbotyra, 2005)
The article examines some of the vocalism features of the Lukšiai subdialect of the Lithuanian West-Aukštaitian (High-Lithuanian) dialect of the Kaunas region. The quality of the first components [i̱], [u̱] of acuted (“falling”) diphthongs were subjected to experimental analysis. The first components [i̱], [u̱] of acuted diphthongs are pronounced half-long in the dialect (the ratio of the length between the first components of acute diphthongs and the short vowels [i̱], [u̱] is 1.6 : 1.0). The quality of the first components [i̱], [u̱] of acuted diphthongs is much variable in the dialect. The components [i̱], [u̱] are pronounced more close at the beginning of the sound and more open at the end of the sound.